Endoscopic bilateral revision after metal stent deployment for hepatic hilar obstruction using molting technique (with videos). (January 2022) - Yamamura, Masahiro; Ogura, Takeshi; Ueno, Saori; Okuda, Atsushi; Nishioka, Nobu; Yamada, Masanori; Ueshima, Kazuya; Matsuno, Jun; Yamamoto, Yoshitaro; Higuchi, Kazuhide
Background: After multiple uncovered self-expandable metal stent (UCSEMS) deployments, endoscopic revision becomes complex and potentially challenging. A novel stent delivery system with a dilation function has recently been developed in Japan. This study evaluated the technical feasibility of this device for patients with unresectable malignant hilar biliary obstruction (MHO) after multiple UCSEMS deployments. Method: Participants comprised consecutive patients with unresectable MHO who had undergone multiple UCSEMS deployments and required endoscopic revision for the right or left hepatic bile ducts, as decided by cholangiography under endoscopic retrograde cholangiopancreatography (ERCP) guidance. Results: A total of 14 patients requiring endoscopic revision of right and left hepatic bile ducts were enrolled in this study. Among these 14 patients, guidewire insertion through the mesh of previously placed stents failed in 2 patients. As a result, these two patients underwent only unilateral UCSEMS deployment. Because clinical success was not obtained, transmural placement of the UCSEMS under Endoscopic Ultrasound (EUS) guidance to the segment of the liver not being drained was performed in those patients. The molting technique was attempted in 12 patients, proving successful in all patients. The technical success rate was therefore 92.8% (12/14). Mean procedure time was 23.2 min. Conclusion: This novel stent delivery system with a dilation function may be useful in endoscopic revision techniques for bilateral UCSEMS deployment.